PENGEMBANGAN MODEL MADRASAH INKLUSIF (Studi atas Kesiapan dan Model Pengembangan Kurikulum Madrasah Inklusif MI AL-Hidayah Margorejo Surabaya) - Mukaffa, Zumrotul - (Program Studi Pendidikan Agama Islam, 2017)
THE DEVELOPMENT OF INCLUSIVE MADRASAH MODEL (A STUDY OF PREPAREDNESS AND DEVELOPMENT MODELS OF INCLUSIVE MADRASAH CURRICULUM IN MADRASAH IBTIDAIYAH AL HIDAYAH MARGOREJO SURABAYA). This research was motivated by the existence of learners in MI Al-Hidayah consisting of regular learners and learners with special needs. It was also conducted considering that in the city of Surabaya, inclusive madrasah model hasn’t been found. This study aims to analyze the preparedness of madrasah towards inclusive madrasah, and to develop one of the products needed in the development of inclusive madrasah that is document product I of inclusive madrasah curriculum. This research used development research model. The results of the research were: first, 100% or all respondents expressed readiness to welcome the change from regular madrasah to inclusive madrasah as proved by the commitment to participate, promote, and avoid resistance to change. Second, document model I of the inclusive madrasah curriculum developed in Madrasah Al-Hidayah based on long term local needs analysis using four models: duplication model, modification, substitution and omission. The four, models are not contained in the curriculum document I MI Al-Hidayah. The four curriculum models will be clarified on the design of PPI, syllabus and RPP (Lesson Plan).